Analysis of the influence of collagen fibres in the dermis on skin optical reflectance by Monte Carlo simulation in a nine‐layered skin model. Issue 2 (13th November 2017) - Masuda, Y.; Ogura, Y.; Inagaki, Y.; Yasui, T.; Aizu, Y.
Abstract: Background: Collagen fibres in the dermis play an important structural role in the skin. Age‐related changes to these fibres cause wrinkles and slackness of facial skin. However, it is not clear how dermal collagen fibres affect skin colour. The purpose of this study was to clarify the influence of altered collagen fibres on skin colour, using both experimental measurement of fibre density and Monte Carlo simulations in an optical model of skin. Methods: Reflection spectra were measured from the cheeks of 12 Japanese women (22‐65 years old) by spectral colorimeter. Two‐dimensional autocorrelation functions were calculated from second harmonics generation (SHG) images acquired from the same locations and used to calculate collagen density indices. Monte Carlo simulations of light reflectance by skin were performed using a nine‐layered model that precisely imitates skin structure. The relationship between dermal collagen fibre density and skin reflection spectra was analysed. Results: A positive correlation was found between collagen density and skin brightness, as measured by the colour value, L * (using the L * a * b * colour space). In addition, collagen density showed a strong inverse correlation with age and with the optical absorption of dermis. The Monte Carlo simulations showed that the reflection spectrum of skin changes when the scattering coefficient of the dermis is altered. These changes were the same for simulated and experimentally measured reflection spectra. Conclusion: When collagen fibre density in the upper dermis is decreased with age, skin colour becomes less bright because light scattering in the skin is decreased.